Tantangan Yang Dihadapi Jaksa Dalam Melakukan Penuntutan Perkara Anak - Simanjuntak, Nadia Teresia; Manullang, Herlina Manullang (Faculty of Law Universitas Lancang Kuning, 2024)
The Attorney General of the Republic of Indonesia for Criminal Affairs has one of the duties and authorities in carrying out Prosecution as stipulated in Article 30 of the Republic of Indonesia Law Number 11 of 2021 which has the following duties: Conducting Prosecution, Implementing Court Decisions, Supervising the Implementation of Criminal Decisions, and Conducting Investigations into Certain Criminal Acts. Prosecutors in handling children's cases face a number of challenges that require a different approach compared to adult cases. The first challenge is to ensure that the prosecution process still pays attention to the best interests of the child, both the perpetrator and the victim, in accordance with the principles of child protection. In addition, prosecutors often have to deal with limitations in evidence and testimony, considering that children as perpetrators or victims may not be able to provide clear and consistent information. This article discusses the challenges faced by prosecutors, ranging from the complexity of proof, the limitations of child-friendly justice, to external pressure from society demanding strict punishment. Through a normative approach and field studies, this article identifies resource gaps, lack of specialized training, and barriers to the implementation of restorative approaches as factors that make it difficult for prosecutors to achieve balanced justice between legal interests and child protection.